Clinical Outcome of Patients with Epithelioid Glioblastoma Harboring BRAFV600E Mutation; A Single Institution Experience - Subramanian, Preethi; Das, Anindita; Chilukuri, Srinivas; Rajendran, Adhithyan; Patil, Sushma; Mullapally, Sujith Kumar; Krishna, Uday; Kumar, Roopesh; Jalali, Rakesh (South Asian Journal of Cancer, 2024)
Epithelioid glioblastoma (GBM) is a rare variant of GBM. The study aimed to look into clinicopathological details and outcomes of patients with epithelioid GBM harboring BRAFV600E mutation from a single institution.Ten cases of epithelioid GBM diagnosed over the past 5 years were reviewed. All patients underwent surgical resection followed by adjuvant treatment as per protocol after initial diagnosis. Of these, seven patients were planned to redo surgery, reradiation, BRAF with MEK inhibitors, and bevacizumab based on clinical condition, magnetic resonance imaging findings, and progression-free survival after their recurrence. Four recurrent patients had received dabrafenib and trametinib.All tumor locations were supratentorial. The median follow-up was 2.3 years and the median time to recurrence was 19 months from the diagnosis (range 4–36 months). Four recurrent patients received BRAF + MEK inhibitors. One patient who started dabrafenib and trametinib experienced local progression after 33 months, followed by lung and bone metastasis. One patient died due to multiple subacute hemorrhages, who was a known case of congenital vascular malformations, and two patients remained disease-free after a year and 2 years.Epithelioid GBM is a very rare, but well-documented entity. Therefore, careful preoperative imaging and detailed evaluation of genetic studies including BRAF V600E mutation are necessary for accurate diagnosis and appropriate selection of treatment for epithelioid GBM. Dabrafenib plus trametinib showed clinically meaningful activity in patients with BRAF V600E mutation-positive recurrent high-grade glioma.
Keywords: epithelioid glioblastoma; BRAF V600E inhibitors